PENGARUH LIVE SHOPPING TIK-TOK TERHADAP KEPUTUSAN PEMBELIAN PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI MEDAN - Alexander Sabastian Pangaribuan; Anggita Kinanti; Ade Mima Zakia Siregar; Etri Br Kaban; Dian Pratiwi; Nurul Wardani (Ekonis: Jurnal Ekonomi dan Bisnis, 2026)
This study analyzes the influence of TikTok's Live Shopping feature on purchasing decisions of students from the Faculty of Economics, State University of Medan. The transformation of social media into a digital marketplace has enabled TikTok, through its live shopping feature, to enable direct interaction between sellers and buyers in real time. A quantitative approach was used with 98 respondents determined using the Slovin formula. Data were collected through a questionnaire and analyzed using normality, linearity, and simple linear regression tests. The results show that TikTok Live Shopping has a positive and significant effect on purchasing decisions, with a regression coefficient (B) of 0.577 and a significance value of 0.000 (0.05). This means that the higher the intensity and quality of the live shopping experience, the greater the student's tendency to purchase. Interactive features such as direct communication, product demonstrations, and real-time promotions increase consumer trust and satisfaction. This study confirms that live shopping is an effective digital marketing strategy, and further research is recommended to add variables such as consumer trust and customer loyalty to deepen the understanding of social commerce behavior in the digital era.Keywords: TikTok Live Shopping, purchasing decisions, digital marketing, Consumer Behavior.